Relation of insulin treatment for type 2 diabetes to the risk of major adverse cardiovascular events after acute coronary syndrome: an analysis of the BETonMACE randomized clinical trial - Gregory G. Schwartz (Cardiovascular Diabetology, 2021)
Abstract Background In stable patients with type 2 diabetes (T2D), insulin treatment is associated with elevated risk for major adverse cardiovascular events (MACE). Patients with acute coronary syndrome (ACS) and T2D are at particularly high risk for recurrent MACE despite evidence-based therapies. It is uncertain to what extent this risk is further magnified in patients with recent ACS who are treated with insulin. We examined the relationship of insulin use to risk of MACE and modification of that risk by apabetalone, a bromodomain and extra-terminal (BET) protein inhibitor. Methods The analysis utilized data from the BETonMACE phase 3 trial that compared apabetalone to placebo in patients with T2D, low HDL cholesterol, andACS. The primary MACE outcome (cardiovascular death, myocardial infarction, or stroke) was examined according to insulin treatment and assigned study treatment. Multivariable Cox regression was used to determine whether insulin use was independently associated with the risk of MACE. Results Among 2418 patients followed for median 26.5 months, 829 (34.2%) were treated with insulin. Despite high utilization of evidence-based treatments including coronary revascularization, intensive statin treatment, and dual antiplatelet therapy, the 3-year incidence of MACE in the placebo group was elevated among insulin-treated patients (20.4%) compared to those not-treated with insulin (12.8%, P = 0.0001). Insulin treatment remained strongly associated with the risk of MACE (HR 2.10, 95% CI 1.42–3.10, P = 0.0002) after adjustment for demographic, clinical, and treatment variables. Apabetalone had a consistent, favorable effect on MACE in insulin-treated and not insulin-treated patients. Conclusion Insulin-treated patients with T2D, low HDL cholesterol, and ACS are at high risk for recurrent MACE despite the use of evidence-based, contemporary therapies. A strong association of insulin treatment with risk of MACE persists after adjustment for other characteristics associated with MACE. There is unmet need for additional treatments to mitigate this risk. Trial registration ClinicalTrials.gov NCT02586155, registered October 26, 2015